THE STUDY OF SIGNIFICANCE OF DIGITAL MARKETING TOOLS IN THE PROMOTION OF e-COMMERCE WESBITES - Deepak Kumar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In different sectors worldwide, digital tools and marketing have become commonly used. These resources enable businesses to acquire real-time insights into consumers and to more efficiently build and convey value to customers. This research aims at understanding the values and practises of sustainable digital marketing through studying the breadth of digital marketing, challenges to its implementation and strategies for developing local digital capacities. Digital media theories, strategies and frameworks of other sectors are adapted and implemented in order to create an innovative and competitive climate for the local land construction sector. A marketing technology adoption model (MTAM) for digital marketing strategies and power growth is described in this research paper. Ease of usage, experience of use, perceived cost experience, higher returns, performance, digital service quality, digital data quality, digital device quality, approach to use and real use are the main factors in this model. Local practitioners support such methods like designing real-time experiences, developing primary value metrics to assess digital marketing, personalization and promoting creativity in the area of digital marketing.